Environmental health case studies at Kampung Pondok Labu, Mukim Keladi, Daerah Kulim / Muhammad Fahmi Zulkifli - Zulkifli, Muhammad Fahmi (2016)
The mission for Kulim District Health Office is to improve hearth of Kulim resident and investigate any cases related to health disease while providing a solution on how to overcome the health problems through assessment, investigation and action. We have decided to choose Kampung Pondok Labu Keladi, Kulim, Kedah as our study location for the community health survey. The community health survey is to collect health data that will be used to develop program that address the priority health problem identify by us. The collected data will be sent to Kulim District Health Office for them to take further action to overcome any health problem that identified through the community health survey activity. The objective of this study is to determine the environmental and villager problem related health at the Kampung Pondok Labu. The study instruments for this study are pH meter, chlorometer, turbidity meter, stationery, community health survey questionnaire, ovitrap, and camera. The data collection of this study are community health survey questioner and interview respondent. The data collected for this study is by using a questioner. The data collection is involve four aspect which is water supply, sewage and drainage system, refuse disposal, pest management and safety and health promotion. Using a graft to present our result for this aspect to shows the data collected from this study. In conclusion, objective of this study had achieve. Most of the villagers had used source of water supply from SADA that most assured because it had treated. So, health of the villager had assured and can avoid them from waterborne disease that carry from water. For solid waste management, majority of the community have their waste collected by the local authority. It is a good practice and should be continue for proper solid waste disposal. The most problem of the villagers for the pest and vector is housefly. Housefly problem become worst especially after rain and fruit season. Besides, this problem may be influenced by the village are near to the poultry farm and there is a cow barn area in the village. Sewage disposal system in Kg. Pondok Labu is still at a manageable levels as they using the soak away pit but at the same time, discharging the sewage water at the same location in the pit which later will percolate into the surrounding soil still can affect and contaminate the underground water.